2022
DOI: 10.1186/s13690-022-00922-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with non-use of modern contraceptives among sexually active women in Ethiopia: a multi-level mixed effect analysis of 2016 Ethiopian Demographic and Health Survey

Abstract: Background Appropriate contraceptive use prevents unintended pregnancy, protects the health of mother and child, and promotes women’s well-being. Use of modern Family planning in Ethiopia was still very low. The purpose of this study was to assess the factors that are associated with non-use of modern family planning services among women of reproductive age. Method A nationally representative 2016 EDHS women data were used for analysis. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…This finding was in line with the findings of a Nepal (Adhikari et al, 2019), Nigeria (Asaolu et al, 2019; Ejembi et al, 2015), and Malawi (Mandiwa et al, 2018) study, which discovered that as women's ages increase, so does their likelihood of using modern contraception. Studies conducted in East Africa (Tessema et al, 2021), China (Wang, 2012), and Ethiopia (Gebeyehu et al, 2018; Mandiwa et al, 2018; Melka et al, 2015b; Mulugeta et al, 2022) found results that differed from the present study. The low contraceptive prevalence among women aged 15 to 24 years is most likely due to the fact that the majority of these women engage in unsafe sex, are newly married, and marriage is based on the institution of producing children.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was in line with the findings of a Nepal (Adhikari et al, 2019), Nigeria (Asaolu et al, 2019; Ejembi et al, 2015), and Malawi (Mandiwa et al, 2018) study, which discovered that as women's ages increase, so does their likelihood of using modern contraception. Studies conducted in East Africa (Tessema et al, 2021), China (Wang, 2012), and Ethiopia (Gebeyehu et al, 2018; Mandiwa et al, 2018; Melka et al, 2015b; Mulugeta et al, 2022) found results that differed from the present study. The low contraceptive prevalence among women aged 15 to 24 years is most likely due to the fact that the majority of these women engage in unsafe sex, are newly married, and marriage is based on the institution of producing children.…”
Section: Discussionmentioning
confidence: 99%
“…By incorporating all community-level variables, the third model (Model II) was developed. Individual-level and community-level factors were included in the 4 th model (model III) [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…The following formula was used to compute it: , where V A represents the variance at the community level, and MOR is always≥ 1. There is no difference between clusters if the MOR is 1 [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Appropriate family planning can prevent both unsafe abortions and unwanted pregnancies. Modern contraceptives are valuable, but not everyone has access to or uses them [ 23 ]. Decisions about family planning have been directly impacted by an increase in the literacy rate, increased opportunities for women to pursue higher education and careers, and improved family socio-economic status [ 24 ].…”
Section: Introductionmentioning
confidence: 99%